Synthesis of Low TENORM Zirconium Sulfate from ZrO(OH)2 with Sulfuric Acid - Rahmatika Alfia Amliliana; Muzakky Muzakky (Universitas Gadjah Mada, 2021)
Zirconium sulfate (ZS) has become one of the alternative chemical compounds for substituting traditional tannery substances using chromium(III) which was not environmentally friendly. The purpose of this research was to synthesize ZS from ZrO(OH)2 using H2SO4 with low Technologically Naturally Occurring Radioactive Material (TENORM) content. This ZS synthesis process shortened the old processing flow at which plenty of chemical reactors were used. The results showed that with 300 mg of feed, 600 mL of 95% H2SO4, at a temperature of 250 °C, the contact time of 150 min, the obtained conversion was 77.76%. Furthermore, in this 95% acid leaching reactor, the SiO2 content was still 2.79% and it was not TENORM free yet, but the FTIR and XRD images were in accordance with BDH standards. Moreover, the quenching process results had been free of SiO2 and TENORM content, but they still contained 1.48% HfO2. The surface of the TEM images from the quenching results had been in the form of elongated and transparent crystals. The result of the economic feasibility analysis showed that the new ZS synthesis process was more economical or profitable when it was compared to the old ZS synthesis process, with a BCR value of 1.258.